MovingU: A prospective cohort study to understand behavioural and environmental contexts influencing physical activity during the transition into emerging adulthood - Matthew Y. W. Kwan; Chloe Bedard; Sara King-Dowling; Sarah Wellman; John Cairney (BMC, 2016)
Abstract Background Children and youth are often considered the most active segment of the population, however, research indicates that physical activity (PA) tends to peak during the adolescent years, declining thereafter with age. In particular, the acute transition out of high school is a period for which individuals appear to be at high-risk for becoming less active. Relatively few studies have investigated the factors influencing the changes in PA during this transition period. Therefore the purpose of the MovingU study is to gain a comprehensive understanding of the behavioural patterns and the socio-ecological factors related to the changes in PA during the transition out of high school. Methods/Design MovingU is comprised of two phases. Phase I is a prospective cohort design and aims to follow 120 students in their last year of high school through to their first year out of high school. Students will be asked to complete questionnaires measuring various psychosocial and socio-environmental variables (e.g., self-efficacy and distress) four times throughout this transition period. Students will also be given a wrist-worn accelerometer to wear for 7-days at each of the four assessments. Phase II is a cross-sectional study involving 100 first-year university students. Students will be asked to complete the same questionnaire from phase I, wear a wrist-worn accelerometer for 5-days, and complete ecological momentary assessments (EMA) using their smartphones at randomly selected times throughout the day for 5-days. EMA items will capture information regarding contextual and momentary correlates of PA. Discussion The MovingU study represents the first to evaluate the social and environmental influences of PA behaviour changes, including the use of intensive real-time data capture strategies during the transition out of high school. This information will be critical in the development of interventions aimed to prevent or attenuate such drastic declines in PA during emerging adulthood period.